Ending Racial Preferences: The Michigan Story - Allen, Carol M. (Lexington Books, 2009)
In 2006, Michigan voters banned affirmative action preferences in public contracting, education, and employment. The Michigan Civil Rights Initiative (MCRI) vote was preceded by years of campaigning, legal maneuvers, media coverage, and public debate. Ending Racial Preferences: The Michigan Story relates what happened from the vantage point of Toward A Fair Michigan (TAFM), a nonprofit organization that provided a civic forum for the discussion of preferences. The book offers a timely 'inside look' into how TAFM fostered dialogue by emphasizing education over indoctrination, reason over rhetoric, and civil debate over protest. Ending Racial Preferences opens with a review of the campaigns for and against similar initiatives in California, Florida, Washington, and the city of Houston. The book then delivers an in-depth historical account of the MCRIDfrom its inception in 2003 through the first year following its passage in 2006. Readers are invited to decide for themselves whether affirmative action preferences are good for America. Carol M. Allen reproduces the remarks delivered at a TAFM debate, along with a compilation of pro and con responses by 14 experts to 50 questions about preferences. This book will be of interest to those working in the fields of public policy and state politics.